Quaternary volcanism in the Yura Monogenetic Field near Arequipa city, southern Peru - Aguilar, Rigoberto; Arteaga, David; Manrique, Nélida; van Wyk de Vries, Benjamin; Cueva, Kevin; Taipe, Edu; Guillou, Hervé; Scao, Vincent (Frontiers in Earth Science, 2022)
In the Peruvian Andes, monogenetic volcanism is less explored and studied than the larger stratovolcanoes, but is widespread. In the area surrounding the town of Yura Viejo, five small volcanic centers have been identified, which together with the previously known Nicholson volcano, form the Yura Monogenetic Field. Phreatomagmatic, Strombolian and effusive eruptions characterize the monogenetic activity of the field. As a result of these eruptions, small scoria cones, maars, and lava flows/coulées were generated. 40Ar/39Ar ages and stratigraphic considerations allow us to place the eruptive activity in the Middle – Upper Pleistocene (c. 195 – 54 ka). The eruptive products show ubiquitous olivine phenocryst-rich (< 10 vol%) set in a fine pilotaxitic groundmass, suggesting rapid ascent of basaltic magmas to the surface controlled by the structural configuration. The rocks lie in a narrow range of basaltic-andesite composition (50.9 to 55.6 wt% SiO2). These compositions are the most mafic Pleistocene - Recent volcanic products identified in the Arequipa basin, along with the least differentiated magmas from the nearby Chachani volcanic cluster. These small volcanoes are located between larger active stratovolcanoes providing valuable geoheritage, and are being developed as geosites to communicate risk through geotourism.